Human herpes virus 6 and endogenous biotin in salivary glands. Issue 9 (September 1992) - Green, M; Sviland, L; Taylor, C E; Peiris, M; McCarthy, A L; Pearson, A D; Malcolm, A J
Abstract : AIMS: To detect the presence of human herpes virus 6 (HHV6) and endogenous biotin in paraffin wax embedded and frozen salivary glands. METHODS: Two stage indirect and streptavidin-biotin immunoperoxidase techniques were used to visualise the antigens. RESULTS: HHV6 could not be shown in any of the tissues. However, considerable endogenous biotin antigenicity was detected in the glandular elements of the paraffin wax embedded material. CONCLUSIONS: Results obtained with avidin-biotin detection systems should be interpreted with caution, especially when glandular epithelium is being stained. This may apply to both immunoperoxidase and in situ hybridisation techniques. The use of an anti-biotin antibody as a standard control should be considered.